Symposium 7: Subjectification and Surveillance within Distributed Work-based Learning - Clouder, Lynn (Proceedings of the International Conference on Networked Learning, 2006)
This paper will focus on the formative stages of the development of several communities of practice with what I thought was a common interest in work-based learning (WBL). Work based learning involves learning at higher education level derived from paid or unpaid work (Garnett, 1997). This definition not only gives some sense of the possible breadth of activities that WBL covers but also the diverse communities of practice that might be involved. Although initially confined within the institution the eventual aim is to extend the communities beyond institutional boundaries facilitated by computer mediated communication. Experiences of scoping WBL and exploring how it is conceptualised by colleagues from a variety of subject disciplines, through face-to-face and online interaction, has drawn attention to issues of identification and positionality. These issues are explored through a conceptual framework of subjectification and surveillance that paradoxically might be argued has generative potential for a community of practice.